2016
DOI: 10.1016/j.ijscr.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Capsular nevus versus metastatic malignant melanoma – a diagnostic dilemma

Abstract: HighlightsThere are many morphologic guidelines to recognize nodal nevus cells, but there are some cases where the prediction of behavior of certain cells may not be accurate solely based on histopathological findings.Advanced histopathological techniques including implementing multiple markers should be employed in scenarios where distinguishing metastatic melanocytes from capsular nevi prove to be difficult.We strongly encourage obtaining a second opinion from a second histopathologist, preferably at a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that these cells, when present in small clusters in the capsule, can be diagnostically challenging on H&E alone when using glass slides. 22,23 They can be even more difficult when reviewed in a digital format where color contrast and focus can be slightly different than when reviewing the corresponding glass slides using a microscope.…”
Section: False-positive Regions Of Interestmentioning
confidence: 99%
“…Previous studies have shown that these cells, when present in small clusters in the capsule, can be diagnostically challenging on H&E alone when using glass slides. 22,23 They can be even more difficult when reviewed in a digital format where color contrast and focus can be slightly different than when reviewing the corresponding glass slides using a microscope.…”
Section: False-positive Regions Of Interestmentioning
confidence: 99%
“…2,4,7 The incidence of BCN has been described in as high as 25% of excised lymph nodes (including SLN biopsies as well as lymphadenectomies) but has more often been reported between 0% and 12%. 2,4,[6][7][8][9][10][11][12][13][14][15][16] BCN have been identified in all lymph node basins but are most frequently described in the axilla. 2,4,5 There are two major hypotheses regarding the presence of BCN: the first proposes that they occur as neural crest progenitors, which migrate and arrest in LNs and the second that benign cutaneous melanocytic lesions are transported through the lymph system (termed benign mechanical transport or benign metastasis).…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 There are two major hypotheses regarding the presence of BCN: the first proposes that they occur as neural crest progenitors, which migrate and arrest in LNs and the second that benign cutaneous melanocytic lesions are transported through the lymph system (termed benign mechanical transport or benign metastasis). 2,4,5,[8][9][10]12,15,17 Differentiating BCN from micrometastasis of cutaneous melanoma can be challenging, and relies on morphology as well as immunohistochemical (IHC) assays and stains. 4,10,[18][19][20] The clinical significance and prognostic implication of incidentally detected BCN in SLNs of patients with melanoma remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies provided single‐centred data, where the same pathologists observed the histology of the SLNB, perhaps resulting in more awareness for INN . INN mostly occur in the capsule or trabeculae of the lymph node, but in rare cases INN occur in the parenchyma of the lymph node which is similar to the location of metastatic melanoma . Consequently, this could provide difficulties in distinguishing INN from metastatic melanoma, certainly for less experienced pathologists, and may lead to an underestimation of the true frequency of INN in our cohort.…”
Section: Discussionmentioning
confidence: 97%